QOLP-27. NEURO-ONCOLOGICAL PATIENTS' AND CAREGIVERS' PSYCHOSOCIAL BURDEN DURING THE COVID-19 PANDEMIC – A PROSPECTIVE STUDY WITH QUALITATIVE CONTENT ANALYSIS. (12th November 2021) - Renovanz, Mirjam; Binswanger, Julia; Kohl, Carolin; Behling, Felix; Noell, Susan; Hirsch, Sophie; Hickmann, Anne-Katrin; Tatagiba, Marcos; Hippler, Melina; Tabatabai, Ghazaleh
Abstract: OBJECTIVE: The COVID-19 pandemic may reinforce psychosocial distress of neuro-oncological patients. We aimed to 1) differentiate the burden caused by the pandemic vs. the tumor and 2) establish topics relevant for brain tumor patients (BTPs) and caregivers. METHODS: Patients and caregivers were prospectively assessed from April 2020 – July 2020 by a 10-item comprising interview over the phone, including qualitative and quantitative questions. They were quantitatively evaluated i.a. by the Distress Thermometer (DT, score 1-10). The qualitative questions were analyzed using structured content analysis: The interview questions defined the main categories. Subcategories were derived by an inductive approach assessing the frequency of patients' and caregivers' answers. RESULTS: A total of 69 patients and 20 caregivers were interviewed; n= 36 were female (49%), mean age was 53 years (range 32-81). Patients' disease-related DT scores were higher than the COVID-19-related DT scores: the median of the disease-related DT score was 7 (range 2-10) vs. median of COVID-19-related distress: 5.0 (range 2-7). Caregivers perceived a higher burden due to the disease (DT median disease: 8; range 2-10 vs. DT pandemic: 3, range 0-10). A total of 5 main and 21 subcategories were elaborated, most frequently mentioned were "restrictions in public and private affairs" (28%), "changes in the psychological well-being" (23%), "limited social interaction by contact restriction" (25%). Subcategories relevant for caregivers were similar to those of BTPs. CONCLUSION: A considerable proportion of patients and caregivers still perceived the brain tumor disease as more burdensome than the pandemic. We established main and subcategories of interview items possibly of great relevance to patients during these difficult times, which could be implemented in the content-related adaption of the psychosocial assessment.